ON THE EXPERIENCE FORMING THE COMPETENCE OF MUSIC LISTENING IN LEARNERS DURING THE LESSONS OF MUSICS (Scientific journal of the Fergana State University, 2023)
The articIe, the provides the necessary consultations and guidance for teachers of musics lesson on formulating the musics listening competence of the students. The creations of our classical musical compositions have been shown in synharmony with the nature.